DIGITAL TRANSFORMATION IN THE SMALL TO MEDIUM INDUSTRIES (IKM) AUTOMOTIVE COMPONENTS IN INDONESIA - Faisal Rahman; Bambang Purwoko; Zulkifli, Zulkifli (Bajang Institute, 2023)
Digital transformation is a new strategy in maintaining business continuity and supporting the stability of SMI players when the conditions of the business environment experience rapid changes, especially in the midst of the Corona Virus Disease 2019 (Covid-19) pandemic.. The research developed a model of the moderating effect of adaptive leadership on the relationship of strategic flexibility to digital transformation by integrating strategic intelligence, workforce transformation, and dynamic capabilities. The study used quantitative methods through questionnaires and Focus Group Discussion (FGD) confirmation and analyzed with Structural Equation Modeling (SEM) assisted by SmartPLS. The research sample is 147 respondents from the Small and Medium Industrial (SMI) players/owners of automotive components in Indonesia. The results show the model development for the influence of strategic intelligence on strategic flexibility that is positive and significant, the effect of workforce transformation on strategic flexibility that is positive and significant, the influence of dynamic capabilities on strategic flexibility that is positive and significant, the influence of strategic intelligence on digital transformation that is positive and significant, the influence of workforce transformation on digital transformation that is positive and significant, the effect of dynamic capabilities on digital transformation that is positive and significant, the influence of strategic flexibility on digital transformation that is positive and significant, and adaptive leadership moderating the relationship between strategic flexibility on digital transformation of automotive component SMIs in Indonesia